Chemical composition and antioxidant activity of ‘Nufar’ basil (Ocimum basilicum L.) essential oil from three municipalities of Tolima, Colombia - López Hernández, Martha; Criollo Nunez, Jenifer; Beltran, Jose Isidro; Sandoval Aldana, Angélica (Elsevier, 2025)
Essential oils are natural compounds with great potential to be used as products with high antioxidant activity. The aim of this research was to determine the chemical composition and antioxidant activity of the Nufar variety basil essential oil from three municipalities in Tolima, Colombia. The essential oil extracted from the leaves of this basil variety using microwave-assisted extraction predominantly comprises linalool (37.9–41.1%), estragole (24.5–33.6%), and 1,8-cineole (5.2–7.6%). The quantities of these compounds are influenced by the plant’s place of origin. Regarding antioxidant activity, the basil essential oil cultivated in the municipality of Honda shows higher antioxidant activity in the DPPH and ABTS⋅+ tests (29.89 ± 4.03 and 9.60 ± 1.74 mg/mL, respectively), compared to the values from the municipalities of Mariquita and Espinal. The Principal Component Analysis applied to the data generated biplots that explain 99.8% of the total variation. These indicate that the essential oils from basil grown in the municipality of Espinal are characterized by having a high IC50 (mg/mL) in the DPPH test. On the other hand, the essential oils of basil cultivated in the municipalities of Honda and Mariquita are distinguished by their high content of monoterpenes and total terpenes. The study concludes that the geographical location significantly impacts the chemical composition and antioxidant activity of basil plants.